Logistics research (Springer, 2009)
Features research in the fields of business logistics and logistics engineering. It presents empirical and conceptual work that advances the development of theory and innovative practices in and for business logistics, logistics engineering and supply chain management, as well as the integration of the various associated disciplines such as management and social sciences, economics, behavioral sciences, operations research, informatics, and other relevant engineering sciences.